Enhancing agriculture and ending poverty: IFPRI and Japan - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
For more than 30 years, Japan has partnered with IFPRI in Africa and Asia, providing support for areas of shared concern—from agricultural modernization to capacity strengthening to nutrition. Evidence from IFPRI research, which has benefited from long-term Japanese support, has influenced policies in the countries of research and informed Japan’s investments in development. This brochure highlights the achievements of our partnership.